Immunogenicity and tolerance induction in vascularized composite allotransplantation - Sun, Jiahui (Angela); Adil, Aisha; Biniazan, Felor; Haykal, Siba (Frontiers in Transplantation, 2024)
Vascularized composite allotransplantation (VCA) is the transplantation of multiple tissues such as skin, muscle, bone, nerve, and vessel, as a functional unit (i.e. hand or face) to patients suffering from major tissue trauma and functional deficits. Though the surgical feasibility has been optimized, issues regarding graft rejection remains. VCA rejection involves a diverse population of cells but is primarily driven by both donor and recipient lymphocytes, antigen presenting cells (APCs), macrophages, and other immune as well as donor-derived cells. Additionally, it is commonly understood that different tissues within VCA, such as the skin, elicits a stronger rejection response. Currently, VCA recipients are required to follow potent and life-long immunosuppressing regimens to maximize graft survival. This puts patients at risk for malignancies, opportunistic infections, and cancers, thereby posing a need for less perilous methods of inducing graft tolerance. This review will provide an overview of cell populations and mechanisms, specific tissue involved in VCA rejection, as well as an updated scope of current methods of tolerance induction.